Mobility of trace elements in pore solutions of Portland cement pastes exposed to leaching - Đuroković, Marija (Array, 2019)
Two Portland cement pastes, CEM I 42.5R and CEM III/A 52.5N were exposed to leaching by soft water throughout a one–year hydration period. Mobility of trace elements was investigated by determination of their pore solution concentration in the course of time. Eleven trace elements were included in this research: antimony, arsenic, cadmium, chromium, cobalt, copper, mercury, nickel, lead, vanadium and zinc. The possible usage of the pore solution trace elements concentration in monitoring of deleterious leaching reactions and prediction of environmental risk was investigated.